BUDIDAYA PUYUH (COTURNIX COTURNIX JAPONICA ) DI PEKARANGAN SEBAGAI SUMBER PROTEIN HEWANI DAN PENAMBAH INCOME KELUARGA - Endah Subekti; Dewi Hastuti (Universitas Wahid Hasyim, 2013)
Yard can provide great benefits to society, because it can planted vegetables, fruit and herbs such as turmeric, lemongrass etc. Yard can also be used as a source of animal protein and an additional source of family income. The advantages of cultivate quail is it has small body size and weighs around 130 grams, short life cycle, high egg productivity ( in the period peak daily egg production can produce about 90 % of the total population in the cage ), feed intake slightly ( about 20 grams / head / day ), easily cultivated and does not require high investment. Quail can deliver results in the form of daily egg production, meat from culled quail ( quail that had stopped laying eggs or egg productivity plummeted start that after about 8 months old ), as well as produce manure that can be processed into organic fertilizer. Yard with an area of approximately 2 m2 can be used to maintain approximately 250 quail at a cost of approximately Rp.3,887,000. With the average cost of feed per month Rp.375,000, of the quail maintenance can provide net income from egg production per day on average Rp.11,500 and income from the sale of quail has not productived Rp.787,500. Based on the advantages of the quail and the results of the economic analysis showed that the cultivation from quail in the yard can provide family income and improve nutrition. Key words : quail, yard, animal protein sources, income